Stereochemistry of tropane alkaloid of convolvine and their derivatives - Turgunov, Kambarali Kuchkarovich; Kadirova, Dilfuza; Okmanov, Rasul; Aripova, Salima Fazilovna; Tashkhodjaev, Bakhodir (European Journal of Chemistry, 2019)
Structures of alkaloid convolvine (1) isolated from Convolvulus subhirsutus and its derivatives-convolamine(N-methylconvolvine) (2) and hydrochloride of N-benzylconvolvine (3) have been determined by single crystal X-ray diffraction technique. Compounds were crystallized in monoclinic space groups having four molecules in unit cell. All compounds contain a bicyclic ring system of tropane, where piperidine rings in all case adopt chair conformation. Hydrogen atom and methyl- and benzyl-substituents located in nitrogen atom of studied compounds occupy equatorial positions. The substituent of tropane core- the veratroyloxy group containing in all compound molecules is an α-axial oriented relative to the tropane core. In crystal structures of compound 1 and 2, the molecules are located in the distance of van der Waals interactions. The H-bond between the anion Cl and the proton of the N atom is observed in the crystal of N-benzylconvolvine hydrochloride (Cl···N 3.337 Å, Cl···H 2.42 Å and Cl-H-N 175°).